ENDOWMENTS, PERCEIVED SIMILARITY, AND DICTATOR GIVING. (19th October 2016) - Goerg, Sebastian J.; Johnson, David B.; Rogers, Jonathan D.
Abstract : A common assumption of money is that it is fungible. An implication of this assumption is that the source of money does not affect economic decision making. We find evidence contradicting this fungibility assumption. Specifically, we explore how the perception of an endowment source influences amounts sent in a dictator game. We find perceived similarity to the endowment provider to be negatively correlated with dictator offers. Dictators who consider themselves relatively more similar to their endowment provider send significantly smaller amounts to their partners. Our results demonstrate that economic decision making can be influenced by the provider of income shocks. ( JEL C78, C91, C99, D31, D64, D74)